Type 2 Innate Lymphoid Cells: Protectors in Type 2 Diabetes - Painter, Jacob D.; Akbari, Omid (Frontiers in Immunology, 2021)
Type 2 innate lymphoid cells (ILC2) are the innate counterparts of Th2 cells and are critically involved in the maintenance of homeostasis in a variety of tissues. Instead of expressing specific antigen receptors, ILC2s respond to external stimuli such as alarmins released from damage. These cells help control the delicate balance of inflammation in adipose tissue, which is a determinant of metabolic outcome. ILC2s play a key role in the pathogenesis of type 2 diabetes mellitus (T2DM) through their protective effects on tissue homeostasis. A variety of crosstalk takes place between resident adipose cells and ILC2s, with each interaction playing a key role in controlling this balance. ILC2 effector function is associated with increased browning of adipose tissue and an anti-inflammatory immune profile. Trafficking and maintenance of ILC2 populations are critical for tissue homeostasis. The metabolic environment and energy source significantly affect the number and function of ILC2s in addition to affecting their interactions with resident cell types. How ILC2s react to changes in the metabolic environment is a clear determinant of the severity of disease. Treating sources of metabolic instability via critical immune cells provides a clear avenue for modulation of systemic homeostasis and new treatments of T2DM.